Viva Zapata! Movie Still - Twentieth Century Fox:::Creator::::::::::::
Enfumio Zapata (Anthony Quinn) and Emiliano Zapata (Marlon Brando) in the movie written by John Steinbeck. RESTRICTED USE Digital copy only. No hard copy.